Mortality patterns in Southern Adriatic islands of Croatia: a registry-based study - Rehberg, Joshua (Croat Med J, 2018)
AIM: To investigate the mortality patterns on the Southern Adriatic islands of Croatia and compare them with those in two, mainly coastal, mainland counties. METHODS: In this registry-based study we used the official mortality register data to analyze the mortality patterns on seven Croatian islands (Brač, Hvar, Korčula, Lastovo, Mljet, Šolta, and Vis) and Pelješac peninsula in the 1998-2013 period and calculated the average lifespan, life expectancy, and standardized mortality ratios (SMR). We compared the leading causes of death with those in the mainland population of two southernmost Croatian counties. RESULTS: The average lifespan of the island population was 3-10 years longer for men and 2-7 years longer for women than that on the mainland. All-cause SMRs were significantly lower for both men and women on Korčula, Brač, Mljet, and Pelješac but significantly higher for women on Šolta (1.22; 95% confidence intervals 1.07-1.38). The leading causes of death on the islands were cardiovascular diseases, with higher percentages in men and lower in women in comparison with those on the mainland. There were no substantial differences in the life expectancy at birth. CONCLUSIONS: Despite longer lifespan, lack of differences in life expectancy at birth suggests that the recent generations of islanders no longer show beneficial mortality patterns, possibly due to diminishing adherence to the Mediterranean diet and lifestyle. Restoring the traditional lifestyles is a public health priority, with the ultimate aim of reducing inequalities and improving the health of island inhabitants.